A country-scale analysis revealed effective land-use zoning affecting forest cover changes in Myanmar. Issue 6 (1st November 2020) - Lwin, Kay Khaing; Ota, Tetsuji; Shimizu, Katsuto; Mizoue, Nobuya
ABSTRACT: The permanent forest estate (PFE) is a tool for maintaining forest areas in perpetuity. The PFE can have several different land-use zones based on different purposes. Here, we evaluated the effectiveness of the PFE in reducing deforestation using country-scale datasets of forest cover change between 2006 and 2017 in Myanmar. We also evaluated the effectiveness of PFE land-use zones such as protected areas (PAs) and production forests in reducing deforestation. The effectiveness was analysed using propensity score matching to minimize the effect of the non-random distribution of the PFE and specific land-use zoning. The results showed that the PFE significantly reduced deforestation compared to non-PFE areas. Within the PFE, both PAs and production forests had lower deforestation than non-PFE. However, both the PFE and non-PFE showed an increased trend of annual deforestation between 2006 and 2017. Production forests also showed an increased trend of annual deforestation although PAs did not. We concluded that the PFE, PAs and production forests are effective in reducing deforestation. However, in Myanmar, further efforts should be undertaken to mitigate the increase of deforestation in the PFE, especially in production forests.